Considering Mining Wastes as a Factor of Increasing the Balance Level of Subsoil Management in Regions - Polyanskaya, Irina Gennadevna; Yurak, Vera Vasilievna; Strovsky, Vladimir Evgenievich (Economy of Regions, 2019)
The importance of considering mining wastes (MW) as a factor of increasing the balance level of subsoil management in regions is growing. Firstly, it happens because of the gradual exhaustion of mineral deposits. Secondly, theformation of significant volumes of mining wastes (regularly generated and already accumulated over a sufficiently long period of time) represents a unique reserve of minerals. These trends are accompanied by the lack of effective waste management programs built on a fundamental theoretical and methodological basis for assessing mining wastes in terms of the balanced subsoil management. One of the key steps is the development of tools for assessing the balance level of subsoil management taking into account MW. An analysis of the domestic and foreign research revealed the lack of works directly related to the development of such methodological approaches. We hypothesise that there is a direct correlation between the creation and use of the fundamental theoretical and methodological basis for assessing MW from the standpoint of the balanced subsoil management (including the methodological tools for assessing the balance level of subsoil management considering MW as a managing tool) and the efficiency of the policy regulating subsoil use and regional waste management. The study’s key result is the creation of the the improved tools for assessing the balance level of subsoil management taking into account MW. We have proven that application of these improved tools for subsoil management increases its efficiency through constant monitoring of the dynamics of the key indicators of the balanced subsoil management. We tested the improved methodological tools for assessing the balance level of subsoil management taking into account MW on the example of the Sverdlovsk Region. The results have demonstrated the indicator of52.62 %. Nevertheless, consideration of mining wastes positively affects the level of subsoil management. That result indicates the importance of considering MW as a source of reproduction of the region’s mineral resources base.